Striving for Life Welfare: Poor Farmers off farm activity in Rural Areas - Tri Cahyono, Sunit Agus (Jurnal Penelitian Kesejahteraan Sosial, 2018)
Viewed from the socio-economic aspect, rural farmer communities are less prosperous than other communities. This fact is concluded based on the results of the research on some farmers in Sendang Mulyo Village, Minggir Subdistrict, Sleman Regency. As an effort to overcome the difficulties of life and to improve social welfare, they make an alternative off farm job. The research on Striving for Life Welfare research, Poor Farmers Off farm activity in Rural Areas is aimed to identify the reasons of farmers in choosing off farm work, and to describe off farm work contributions to family welfare. Data collection drawn from informants was carried out purposively to 30 farmers who have off farm work. The data is analyzed in qualitative descriptive technique. The results of the research show that off-farm job selection is largely not only because of the high burden of family economy that is not proportional to the level of family income, but it has also created economic and psychological pressure. Off farm work is able to contribute to the social welfare of poor farmer families with an indication of the ability to improve the capability to meet the needs of family life. It is recommended to the Ministry of Social and local district government to empower the potential by creating employment opportunity strategies for poor farmers by considering the ability of poor farmers’ families, the community needs, and that of potential of social welfare resources systems that can be developed into productive economic enterprises in rural areas.